1992
DOI: 10.1177/172460089200700202
|View full text |Cite
|
Sign up to set email alerts
|

Serum AFP, hCG and CEA in the Management of Patients with Testicular, Ovarian and Extragonadal Germ Cell Tumors

Abstract: Serum levels of AFP, hCG and CEA were initially and serially measured in 59 patients with testicular germ cell tumors, and serially in 37 with ovarian and 3 with extragonadal germ cell tumors. Patients with seminoma/dysgerminoma or mature teratoma had normal serum AFP and sporadically slightly elevated hCG. Some patients with embryonal carcinoma, pure or with admixture of seminoma, had serum AFP elevated to maximum 100 U/ml, yet its use for monitoring therapy was limited. Patients with yolk sac tumors had elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
1
0
1
Order By: Relevance
“…This was inconsistent with the results of continuous variable analysis. To our knowledge, there is no globally accepted standard cut-off value of tumour markers for cancer screening at present, although previous research has indicated that AFP is commonly used as a tumour marker to help to detect and diagnose cancers of the liver, testicles and ovaries 37 38 and CA724 has a potential in diagnosis of gastric cancer. 9 We cannot provide strong evidence to determine that H. pylori infection plays a role in the cancer process with our limited results.…”
Section: Discussionmentioning
confidence: 99%
“…This was inconsistent with the results of continuous variable analysis. To our knowledge, there is no globally accepted standard cut-off value of tumour markers for cancer screening at present, although previous research has indicated that AFP is commonly used as a tumour marker to help to detect and diagnose cancers of the liver, testicles and ovaries 37 38 and CA724 has a potential in diagnosis of gastric cancer. 9 We cannot provide strong evidence to determine that H. pylori infection plays a role in the cancer process with our limited results.…”
Section: Discussionmentioning
confidence: 99%
“…Χρησιμεύει, όμως, στην διάγνωση, παρακολούθηση, πρόγνωση και ταξινόμηση πολλών κακοήθων νόσων. Έχει χρησιμοποιηθεί στα νεοπλάσματα του γαστρεντερικού [101][102][103][104][105] , παγκρέατος 106 , πνεύμονος 107,108 , μαστού 109 , ωοθηκών 110 , ενδομητρίου 111 , προστάτου 112 , όρχεων 113 , ουροδόχου κύστης 114 , θυρεοειδούς 115 , κοκ. Η ευαισθησία του είναι περίπου 80% (διακύμανση 17-89%) και η εξειδίκευσή του 70% (διακύμανση 34-91%) 96 .…”
Section: δ11 καρκινοεμβρυϊκό αντιγόνο (Cea)unclassified